2018
DOI: 10.1177/2050640618756124
|View full text |Cite|
|
Sign up to set email alerts
|

Receptor‐interacting protein kinase 3 mediates macrophage/monocyte activation in autoimmune hepatitis and regulates interleukin‐6 production

Abstract: Background: The mechanisms of macrophages/monocytes in autoimmune hepatitis (AIH) remain unclear. We investigated the role of receptor-interacting protein kinase 3 (RIP3), a key inflammatory signal adapter, in macrophage/monocyte activation in AIH. Methods: Liver tissues and monocytes from patients were collected to evaluate the relationship between macrophage activation and RIP3 by double-immunofluorescence and Western blotting. RAW264.7 macrophages were used to study the regulation of RIP3 signaling on infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…RIP3 has been increasingly recognized as a key inflammatory signal adapter, which mediates inflammation through necroptosis as well as non-necroptosis function ( 30 , 48 ). Our previous studies have found that RIP3 signaling was involved in macrophage/monocyte activation in the liver tissues of AIH patients and is correlated with the levels of serum hepatic enzyme ( 29 ). Then, we examined the activation of RIP3 and MLKL (the direct downstream effector of RIP3) in liver macrophages of the mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RIP3 has been increasingly recognized as a key inflammatory signal adapter, which mediates inflammation through necroptosis as well as non-necroptosis function ( 30 , 48 ). Our previous studies have found that RIP3 signaling was involved in macrophage/monocyte activation in the liver tissues of AIH patients and is correlated with the levels of serum hepatic enzyme ( 29 ). Then, we examined the activation of RIP3 and MLKL (the direct downstream effector of RIP3) in liver macrophages of the mice.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly accepted that macrophages are implicated in the pathological inflammation and fibrosis of liver diseases and activated macrophages are present in the portal area of AIH ( 26 28 ). Our previous studies have found that receptor-interacting protein kinase 3 (RIP3) signaling was involved in LPS-induced macrophage/monocyte activation in AIH ( 29 ). RIP3 kinase activity supports the recruitment of the mixed lineage kinase domain-like (MLKL) to trigger membrane leakage with the consequent production of pro-inflammatory cytokines ( 1 , 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of RIP3 expression has been described in AIH and other immune disorders and supposed to contribute to the progression of the pathology [45,46]. Zhang et al [31] showed that the accumulated macrophages express RIP3 in AIH liver tissues. And RIP3 deletion has been reported to protect against ConA-induced immune hepatitis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Receptor interacting protein kinase 3 (RIP3) is a molecular switch between tumor necrosis factor (TNF)-induced apoptosis and necrosis [30]. We previously showed that RIP3 signaling is highly correlated with serum transaminase levels in patients with AIH, indicating that RIP3 signal plays important roles in the pathogenesis of the disease [31]. On the other hand, RIP3 also targets and delivers negative signals to MDSCs recruitment in tumor research [32,33].…”
Section: Ivyspringmentioning
confidence: 99%
“…1A). [47][48][49] To analyze the purity of the isolated primary hepatocytes and macrophages, a western blot against CD68 and albumin was performed from the same lysates.…”
Section: Ripk3 Promoter Methylation Protects Hepatocytes From Necroptmentioning
confidence: 99%